The response of Bronchus associated lymphoid tissue (BALT) and thymus following oral admministration of Pasteurella multocida type B:2 in rats - Noziah Ghani.
This experimental study was carried out in 12 adult Spraque Dawley rats weighing between 150-250 gram with the aim to observe the response of Bronchus-associated lymphoid tissue (BALT) and thymus following oral administration of Pasteurella multocida B:2. The rats were divided into two groups which consist of 6 rats each group. For the infected group, 0.5ml of 10 cfu of formalin-killed Pasteurella multocida B:2 was administered directly into the stomach through esophagus by using stomach tube, while for the control group 0.5ml of sterile normal saline was administered into the stomach using the same method. Sample of the lungs from the cranial lobe, middle lobe, caudal lobe of the right lung as wee=ll as the thymus were taken for higtological examination. Using Hematoxylin-eosin staining, the intraepithelial lymphocyte of foliicles associated epithelium (FAE) was counted manually. Methylgreen Pyronin staining was used to count the plasma cells. The results were analyzed statistically using t-test. The results showed there were significant differences (p<0.05) in intraepithelial lymphocyte and plasma cells count between the control group and the infected group. The IEL and plasma cells counts were higher in the infected group as compared to the control group.